Latecomer Economies and National Digital Policy: An Industrial Policy Perspective. Issue 7 (2nd July 2020) - Foster, Christopher; Azmeh, Shamel
Abstract: The global economy is experiencing digital transformation with impacts felt in developing countries. Digital firms and capabilities, however, remain concentrated in advanced economies. These processes indicate an emerging source of global economic inequality and a widening of the technological gap. Recently, there has been a growth in interventionist digital policy in developing and emerging economies but research has so far made a limited analysis of how this might fulfil economic objectives and support technological catch-up. In this paper, we examine this growth of national digital policies and highlight how industrial policy objectives are important drivers of digital strategies. Examining a number of cases based on an extensive analysis of national digital policies, with a focus on China, we illustrate that these policies often aim at facilitating global integration and linkages. However, our analysis shows that, under certain conditions, more interventionist approaches can be vital in countering structural challenges. Challenges include the power of digital platforms, limitations of domestic digital firms, and limited ability to leverage digitalisation for broad-based national development.